Cartilla para la integración de un sistema de gestión global Gap e NTC-ISO 14001 para el sector porcícola - Moreno Piernagorda, Linda Johana; Pacheco Corredor, Beatriz Adriana (Escuela Colombiana de Ingeniería Julio Garavito, 2014)
The realization of this work focuses on the pork industry in Colombia which today faces many challenges, because with the signing of free trade agreements - NAFTA, there has been an increase in imports of different products to our country. This has forced the production systems of pig farmers to be more efficient and more rigorously certified or fulfilled some systems, for this reason it was decided to create an educational booklet for the integration of a management system NTC-ISO14001, GLOBAL GAP , drawing as objectives the identification of priority points for the integration of the two models, the establishment of the requirements of the models for the sector in order to be able to integrate them in the porcicolas farms, in addition to this aligned to the requirements of the structure of high level of the future expedition of the norm 14001: 2015. These two are taken because Global Gap contains in its structure the three goals, quality, environment and welfare of the working personnel, additional to this is a norm that focuses on agricultural sectors this will integrate the NTC-ISO 14001 since it is of great importance because the amount of excreta (feces + urine + water) that is p roduce in a pig farm affects the microenvironment (the granjamisma) and the environment in general.For the preparation of this booklet is part of a documentary research, using information collected on different sectors producers who have applied the educational methodology of the booklet and thus be able know the didactic presented by the existing material The importance of a book as a method to transmit these systems was that education levels are low in rural areas and where the primary sector of the country is located, in this case the livestock sector. In addition to this, their educational situation is determined by two critical elements: the conditions of poverty of the population, at a clear disadvantage in terms of quality of life and access to public services vis-à-vis the urban population and, on the other hand, the prevalence of Critical situation of public education in Colombia in terms of the quality levels it offers (deficiencies in content, methodologies and management), bearing in mind that in the supply of educational services in the rural sector, official education predominates, which has given As a result, out of every three young people in the city, only one is in the field. It was concluded that the integration model managed for the livestock sector is viable, since the global gap standard covers many aspects of ISO standards, which is easy to integrate with them and is very practical for the sector because its emphasis is only agricultural.

La realización de este trabajo se enfoca al sector de la porcicultura en Colombia el cual hoy enfrenta muchos retos, pues con la firma de los tratados de libre comercio - TLC, se ha generado aumento de importaciones de diferentes productos a nuestro país. Esto ha obligado a que los sistemas productivos de los porcicultores sean más eficientes y se certifiquen o cumplan con mayor rigor algunos sistemas, por esta razón se decidió la creación de una cartilla educativa para la integración de un sistema de gestión NTC-ISO14001, GLOBAL GAP, trazando como objetivos la identificación de puntos prioritarios para la integración de los dos modelos, el establecimiento de los requisitos de los modelos para el sector con el fin de poderlos integrar en las granjas porcicolas, además de esto alineados a los requisitos de la estructura de alto nivel de la futura expedición dela norma 14001:2015.Se toman estas dos nomas debido a que Global Gap contiene en su estructura las tres metas, calidad, medio ambiente y bienestar del personal trabajador, adicional a esto es una norma que se enfoca a sectores agropecuarios esto se integrara la NTC-ISO 14001puesto que es de gran importancia debido a que la cantidad de excreta (heces + orina +agua) que se producen en una explotación porcina afecta al microambiente (la granjamisma) y al ambiente en general.Para la elaboración de esta cartilla se parte de una investigación documental, utilizando información recolectada sobre diferentes sectores productores que han aplicado la metodologÍa educativa de la cartilla y asÍ poder conocer la didáctica presentada por el material existente La importancia de una cartilla como método para trasmitir dichos sistemas radico en que los niveles de educación son bajos en el ámbito rural y donde además se ubica el sector primario del paÍs, en este caso el sector pecuario. Adicional a esto, su situación educativa está determinada por dos elementos crÍticos: las condiciones de pobreza de la población,en clara desventaja en cuanto a la calidad de vida y acceso a servicios públicos frente ala población urbana y de otro lado, la prevalencia de una situación crÍtica de la educación pública en Colombia en cuanto a los niveles de calidad que ofrece (deficiencias de contenidos, metodologías y gestión), teniendo en cuenta que en la oferta de servicios educativos en el sector rural predomina la educación oficial, lo que ha dado como resultado que de cada tres jóvenes escolarizados en la ciudad solo uno hay en el campo.Se llegó a la conclusión de que el modelo de integración manejado para el sector pecuario es viable, pues la norma global gap abarca muchos aspectos de las normas ISO, que es fácil de integrar con las mismas y es muy práctico para el sector pues su énfasis es solo agropecuario.
Keywords: Calidad; Sistemas integrados de gestión; Medio Ambiente; Normas; Environmental; Quality; Integrated Management Systems; Norms